Modeling and Simulation of the Driver's Biomechanical System using Adams Software : Array - Amortila , Valentin; Mereuta , Elena; Novetschi, Monica; Rus, Madalina (Journal of Danubian Studies and Research, 2021)
This paper presents a way of approaching the modeling of multibody systems. The proposed model tries to reproduce as closely as possible the driver's skeletal system when a series of commands are activated on board the vehicle. Elements of this model were imported into the AutoCAD computer graphics program as polyface mesh entities. We transformed the entities into solid with the Inventor program by exporting from AutoCAD with the extension .iges and importing them into the Inventor program. The solid model made with the help of the Inventor program was exported again with the extension .dwg in AutoCAD. The result was 222 solid elements (corresponding to each human bone) for which the import procedures were followed in the MSC ADAMS software. With the help of STEP motion laws, we simulated changing the gears of the vehicle on the virtual model. The verification analysis at the end of the simulation showed that the created model has 104 degrees of freedom, 53 moving elements, 20 simple rotational couplings, 2 spherical rotational couplings, 15 fixed joints, 18 imposed movements and that all the kinematic restrictions introduced are valid. The virtual model created can be a tool for analyzing the biomechanical system of the driver for car manufacturers in order to improve the ergonomics of the seat.